Modelling and Assessing Energy Performance of an Urban Transport System with Electric Drives - Felea, Ioan; Csuzi, Istvan; Barla, Eva (Promet - Traffic&Transportation, 2013)
Energy conservation is one of the key priorities of sustainable development strategy. Transport systems are responsible for about one third of energy consumption. As result, the identification of solutions to reduce energy consumption in these systems is essential for the implementation of the sustainable development strategies. The present work is dedicated to identifying the possibilities for a reduction in the consumption of electric energy in electric urban public transport systems, using the audit of their electricity system. After justifying the importance of these concerns, a mathematical model of the electrical energy balance of the electric urban public transport system and its components is presented. The analysis is applied to determine the losses in the system components and useful energy, based on the evaluation and energy consumption measurements. The measurements to reduce energy losses are identified and characterized under technical and economic aspect, optimal electrical energy balances being done on this basis.